2020
DOI: 10.1007/s43545-020-00009-1
|View full text |Cite|
|
Sign up to set email alerts
|

Teachers’ use of class talk interaction as a predictor of learning outcomes in chemistry

Abstract: There appears to be a general, global trend of many students not taking chemistry related courses at post-secondary institutions, while the academic performance of the subject at secondary level is on the decline. Addressing the performance and unpopularity gaps of the subject requires an exploration of effective pedagogical practices. One critical objective of a chemistry teacher is to create an active learning environment. However, due to insufficient research, relatively little is known about the concept an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Other work by Fraser and Lee (2015) has indicated that student attitude is partially responsible for student achievement, while other factors such as self-efficacy, motivation and the learning environment were also significant contributors. To explore the potential impact of these additional factors, a range of studies have been conducted to evaluate the attitude of students and/or their achievement in chemistry from different perspectives and dimensions such as gender-based differences (Steegh et al, 2021), the influence of teacher practices (Mwangi et al, 2020), the self-efficacy of students (Kadioglu-Akbulut and Uzuntiryaki-Kondakci, 2021) and their experiences in learning chemistry (Kaur and Vadhera, 2021;Naiker et al, 2021). Most notably, Celik (2018) showed that providing students with an interactive and engaging learning environment only enhance their achievement if they had a positive attitude toward the topic, otherwise no improvement in achievement was observed.…”
Section: Student Attitude Toward Science Subjectsmentioning
confidence: 99%
“…Other work by Fraser and Lee (2015) has indicated that student attitude is partially responsible for student achievement, while other factors such as self-efficacy, motivation and the learning environment were also significant contributors. To explore the potential impact of these additional factors, a range of studies have been conducted to evaluate the attitude of students and/or their achievement in chemistry from different perspectives and dimensions such as gender-based differences (Steegh et al, 2021), the influence of teacher practices (Mwangi et al, 2020), the self-efficacy of students (Kadioglu-Akbulut and Uzuntiryaki-Kondakci, 2021) and their experiences in learning chemistry (Kaur and Vadhera, 2021;Naiker et al, 2021). Most notably, Celik (2018) showed that providing students with an interactive and engaging learning environment only enhance their achievement if they had a positive attitude toward the topic, otherwise no improvement in achievement was observed.…”
Section: Student Attitude Toward Science Subjectsmentioning
confidence: 99%
“…In addition, Khusnaini (2019) and Tsegaw (2019) stated that it is proved to be more practical to utilize. It is because it has clear guidelines and flexible that makes it open for modification (Mwangi et al, 2021).…”
Section: 1introductionmentioning
confidence: 99%
“…Huriyah and Agustiani (2018) stated that FIACS offers a robust and reliable tool to record classroom interaction. Moreover, it is proved to be more practical and simple to utilize (Khusnaini, 2019;Tsegaw, 2019) because it has clear guidelines (Huriyah & Agustiani, 2018) and has flexible nature which makes it open for adaptation and modification (Mwangi et al, 2021;Qassim, 2017;Tsegaw, 2019). Some of the recommended guidelines for utilizing FIACS mentioned previously will be provided.…”
Section: Introductionmentioning
confidence: 99%